Piperine Reduces Neoplastic Progression in Cervical Cancer Cells by Downregulating the Cyclooxygenase 2 Pathway - Luana Pereira Cardoso; Stefanie Oliveira de Sousa; Juliana Prado Gusson-Zanetoni; Laura Luciana de Melo Moreira Silva; Barbara Maria Frigieri; Tiago Henrique; Eloiza Helena Tajara; Sonia Maria Oliani; Flávia Cristina Rodrigues-Lisoni (MDPI AG, 2023)
Cervical cancer is the fourth-most common type of cancer in the world that causes death in women. It is mainly caused by persistent infection by human papillomavirus (HPV) that triggers a chronic inflammatory process. Therefore, the use of anti-inflammatory drugs is a potential treatment option. The effects of piperine, an amino alkaloid derived from Piper nigrum, are poorly understood in cervical cancer inflammation, making it a target of research. This work aimed to investigate the antitumor effect of piperine on cervical cancer and to determine whether this effect is modulated by the cyclooxygenase 2 (PTGS2) pathway using in vitro model of cervical cancer (HeLa, SiHa, CaSki), and non-tumoral (HaCaT) cell lines. The results showed that piperine reduces in vitro parameters associated with neoplastic evolution such as proliferation, viability and migration by cell cycle arrest in the G1/G0 and G2/M phases, with subsequent induction of apoptosis. This action was modulated by downregulation of cyclooxygenase 2 (PTGS2) pathway, which in turn regulates the secretion of cytokines and the expression of mitogen-activated protein kinases (MAPKs), metalloproteinases (MMPs), and their antagonists (TIMPs). These findings indicate the phytotherapeutic potential of piperine as complementary treatment in cervical cancer.